2008
DOI: 10.1287/mnsc.1080.0910
|View full text |Cite
|
Sign up to set email alerts
|

Social Preferences and Supply Chain Performance: An Experimental Study

Abstract: Supply chain contracting literature has traditionally focused on aligning incentives for economically rational players. Recent work has hypothesized that social preferences, as distinct from economic incentives, may influence behavior in supply chain transactions. Social preferences refer to intrinsic concerns for the other party's welfare, reciprocating a history of a positive relationship, and intrinsic desires for a higher relative payoff compared with the other party's when status is salient. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
281
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(289 citation statements)
references
References 39 publications
8
281
0
Order By: Relevance
“…Recent studies indicate that a social preference may influence behaviour in supply chain transactions. Loch and Wu (2008) have developed a game structure for a linear contract between a wholesale price, and order quantity and market price. Their results suggested that there are social preferences in business transactions.…”
Section: Procurementmentioning
confidence: 99%
“…Recent studies indicate that a social preference may influence behaviour in supply chain transactions. Loch and Wu (2008) have developed a game structure for a linear contract between a wholesale price, and order quantity and market price. Their results suggested that there are social preferences in business transactions.…”
Section: Procurementmentioning
confidence: 99%
“…Loch and Wu (2008) use laboratory experiments with human subjects to show that profit comparisons Article submitted to ; manuscript no.…”
Section: Figurementioning
confidence: 99%
“…In this paper, we characterize the agent's unfairness aversion preference based on the utility function proposed in literature [31]. Numerous scholars found that agents in a weak position, in addition to paying more attention to their own profits, are much willing to compare with other agents [2,32]. In China's project practice, compared to the owner, the contractor generally is in a weak position.…”
Section: Inequity Aversion Modelmentioning
confidence: 99%
“…In the negotiation process about construction time compression, the distribution and comparison of benefits will trigger the perceptions of fairness between the owner and the contractor, which will have a significant impact on the negotiation process and results. In addition, many scholars found that the subjects who are in a weak position not only care about their own benefits but also compare their benefits to others [1,2]. In the construction practice of China, the contractor is in a weak position generally compared with the owner.…”
Section: Introductionmentioning
confidence: 99%